2012
DOI: 10.1073/pnas.1115307109
|View full text |Cite
|
Sign up to set email alerts
|

Atomically precise gold nanocrystal molecules with surface plasmon resonance

Abstract: Since Faraday's pioneering work on gold colloids, tremendous scientific research on plasmonic gold nanoparticles has been carried out, but no atomically precise Au nanocrystals have been achieved. This work reports the first example of gold nanocrystal molecules. Mass spectrometry analysis has determined its formula to be Au 333 ðSRÞ 79 (R ¼ CH 2 CH 2 Ph). This magic sized nanocrystal molecule exhibits fcc-crystallinity and surface plasmon resonance at approximately 520 nm, hence, a metallic nanomolecule. Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
254
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(267 citation statements)
references
References 37 publications
11
254
0
1
Order By: Relevance
“…Generally, metal nanomaterials were used to immobilize biomolecules due to their bio-conjugation ability, or used as catalysts to activate the electrochemical process. Many researches related to electrochemical sensors based on metal nanoparticles have mentioned that the metal loading, particle-size and stability had significant effects on the sensing performance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, metal nanomaterials were used to immobilize biomolecules due to their bio-conjugation ability, or used as catalysts to activate the electrochemical process. Many researches related to electrochemical sensors based on metal nanoparticles have mentioned that the metal loading, particle-size and stability had significant effects on the sensing performance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important at low energy where the intensity of the two small peaks at 1.36 and 1.50 eV, shown below to reflect the contribution of the 'staples' in the ligands, are overestimated in the calculation. An earlier report on the smaller Au 25 and Au 38 clusters 32 found that cooling causes an enormous increase in cross-section in the low-energy range (1.0-1.5 eV). Therefore, in addition to the emergence of the two peaks from the rather smooth spectrum at room temperature as demonstrated in our measurement (see Fig.…”
Section: Articlementioning
confidence: 99%
“…The prevalent view in recent decades has been that noble-metal clusters of intermediate size-that is, those with more than a few dozen but fewer than B10 3 metal atoms-necessarily have featureless optical absorption spectra of low information content in the near-IR, VIS and near-UV regions. At most, one expects a broad, smooth LSPR feature 25,26 . High information content is expected only in the mid-IR region 27 .…”
mentioning
confidence: 99%
“…Mass spectrometry analysis has determined the formula of gold nanocrystal molecules to be Au333(SR)79 (Qian et al 2012). This metallic nanocrystal molecule exhibits fcc-crystallinity and surface plasmon resonance (SPR) at ~7 to 720 nm.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%